Critical success factors of total productive maintenance implementation in Malaysian automotive SMEs - Mohd Yusoff, Badli Shah (2010)
Total Productive Maintenance (TPM) has been recognized widely and accepted by many organizations as a management philosophy. Currently, the implementation level of TPM mainly concentrated within the large industries with few Small and Medium Enterprises (SMEs) adopting the TPM. Thus, this research aims to determine the level of TPM implementation in automotive SMEs. This research examines the Critical Success Factors (CSFs) level of importance and practices, and the barriers associated in implementing TPM. Eventually, the identified CSFs are to assist the SMEs in implementing TPM to further enhance their production equipment maintenance activities. A survey methodology was employed in this study adopting various stages involving review of literature, design and development of survey questionnaire, data collection, data analysis and discussions. The study showed 87% of responses have implemented TPM more than 3 years and also they are having good knowledge of TPM philosophy, aims and goals. However, success implementation was found not very encouraging. With only 10.64% strongly agree that they have implemented TPM successfully. Analysis of the TPM CSFs revealed that all factors of CSFs, Training and Education, Top Management Commitment, Performance Management System, Resource Management, Continuous Improvement System, and Work Culture and Involvement are important in ensuring successful implementation. Majority of the respondents also agree that these factors are the key success factors for successful TPM implementation. However, the Training and Education and Top Management Commitment are the two highest factors that are not widely being practiced within automotive SMEs. Responses from the respondents revealed that among the highest barriers in the TPM implementation was Lack of long term vision and strategic planning, followed by Lack of management support and Lack of understanding. These barriers are the constraints needed to be addressed through the CSFs if the success of TPM is required. Finally, the analysis of the significant relationship between TPM CSFs and TPM Outcomes shows the TPM CSFs significantly influenced the TPM Outcomes. It can be seen that there are variations of 93.7%, 55.4% and 39.6% towards the three measured variables of Overall Equipment Effectiveness, Autonomous Maintenance and Planned Maintenance respectively. These results show that if the TPM CSFs which were considered important are able to be translated into practice; most probably the success of TPM will be observed.